The behavioural phenotype of 14-month-old female TAU58/2 transgenic mice - Kreilaus, Fabian; Masanetz, Rebecca; Watt, Georgia; Przybyla, Magdalena; Ittner, Arne; Ittner, Lars; Karl, Tim (Behavioural Brain Research, 2021)
Frontotemporal dementia (FTD) and Alzheimer's disease (AD) exhibit intracellular inclusions [neurofibrillary tangles (NFT's)] of microtubule-associated protein tau that contributes to neuronal dysfunction and death. Mutations in the microtubule-associated protein tau (MAPT) gene leads to tau hyperphosphorylation and promotes NFT formation. The TAU58/2 transgenic mouse model expresses mutant human tau (P301S mutation) and exhibits behavioural abnormalities relevant to dementia in early adulthood. Here we comprehensively determined the behavioural phenotype of TAU58/2 transgenic female mice at 14 months of age using test paradigms relevant to FTD and AD. TAU58/2 females showed a significant motor deficit and lower bodyweight compared to WT littermates. Transgenic females failed to habituate to the test arena in the light-dark test. Interestingly, transgenics did not exhibit an anxiolytic-like phenotype and intermediate-term spatial learning in the cheeseboard test was intact. However, a significant learning deficit was detected in the 1st trial across test days indicating impaired long-term spatial memory. In addition, the preference for a previously rewarded location was absent in transgenic females during probe trial testing. Finally, TAU58/2 mice had a defective acoustic startle response and impaired sensorimotor gating. In conclusion TAU58/2 mice exhibit several behavioural deficits that resemble those observed in human FTD and AD. Additionally, we observed a novel startle response deficit in these mice. At 14 months of age, TAU58/2 females represent a later disease stage and are therefore a potentially useful model to test efficacy of therapeutics to reverse or ameliorate behavioural deficits in post-onset tauopapthy-related neurodegenerative disorders.
Created from Fastlane, Scopus look-up
Keywords: Alzheimer's disease; Behaviour; Female; Frontotemporal dementia; TAU58/2 transgenic mouse; Tauopathy